Ultrathin Nanobelts as an Excellent Bifunctional Oxygen Catalyst: Insight into the Subtle Changes in Structure and Synergistic Effects of Bimetallic Metal–Organic Framework. Issue 12 (17th September 2018) - Xiao, Xiao; Li, Qing; Yuan, Xinya; Xu, Yuxia; Zheng, Mingbo; Pang, Huan
Abstract: In recent years, increasing attention has been paid to metal–organic frameworks by scientists working in the field of electrocatalytic material chemistry. Herein, using the hydrothermal method, ultrathin Ni/Co bimetallic metal–organic framework nanobelts that can be directly adopted as highly efficient electrocatalysts are prepared. The optimized Ni/Co ultrathin nanobelts can reach an onset potential of 0.939 V [these values are very close to those of Pt/C (0.940 V)] and show superior stability relative to that of Pt/C toward oxygen reduction reaction (ORR). Additionally, under the current density of 10 mA cm −2, the Ni/Co ultrathin nanobelts show the potential of 1.478 V for oxygen evolution reaction (OER), which is much better than that of IrO2, indicating the large potential of the metal–organic frameworks as a bifunctional oxygen catalyst in metal–air batteries. In addition, after OER and ORR, the color of the Ni/Co ultrathin nanobelts sample is slightly lighter, and it can be seen that the channel becomes blurred but still exists. The X‐ray diffraction, infrared spectrometry, and X‐ray photoelectron spectroscopy results for Ni/Co ultrathin nanobelts before and after catalysis are basically identical. The findings suggest that the ultrathin belt‐like structure and the synergy effect between Ni and Co are crucial for tuning the electrocatalytic activity. Abstract : Bimetallic ultrathin metal–organic framework nanobelts represent one kind of promising power materials for electrocatalytic material chemistry. Facile one‐step hydrothermal synthesis strategies, high electrocatalysis activity, and excellent stability are prominent features of oxygen reduction reaction and oxygen evolution reaction. The electrocatalysis activity of the metal–organic framework nanobelts can be adjusted by controlling the introduction of Co content.